Exploration of the Relationship Between Gut Microbiota and Polycystic Ovary Syndrome (PCOS): a Review - Zhao, Xiaoxuan; Jiang, Yuepeng; Xi, Hongyan; Chen, Lu; Feng, Xiaoling (Geburtshilfe und Frauenheilkunde, 2020)
Polycystic ovary syndrome (PCOS) is an endocrine and metabolic syndrome (MS) with a complex etiology, and its pathogenesis is not yet clear. In recent years, the correlation between gut microbiota (GM) and metabolic disease has become a hot topic in research, leading to a number of new ideas about the etiology and pathological mechanisms of PCOS. The literature shows that GM can cause insulin resistance, hyperandrogenism, chronic inflammation and metabolic syndrome (obesity, diabetes) and may contribute to the development of PCOS by influencing energy absorption, the pathways of short chain fatty acids (SCFA), lipopolysaccharides, choline and bile acids, intestinal permeability and the brain–gut axis. As part of the treatment of PCOS, fecal microbiota transplantation, supplementation with prebiotics and traditional Chinese medicine can be used to regulate GM and treat disorders. This article reviews possible mechanisms and treatment options for PCOS, based on methods which target the GM, and offers new ideas for the treatment of PCOS.
Keywords: polycystic ovary syndrome; gut microbiota; metabolic syndrome; treatment